Uji Fitopatogenitas, Hemolisis serta Kemampuan Mikrob dalam Melarutkan Fosfat dan Kalium: Test of Phytopathogenicity, Hemolysis and Microbial Ability in Solubilizing Phosphate and Potassium - Desak Ketut Tristiana Sukmadewi; Iswandi Anas; Rahayu Widyastuti; Ania Cintaresmini (Jurnal Ilmu Tanah dan Lingkungan, 2017)
Soil microbes have an important role in the cycle of phosphorus and potassium. Therefore, a multifunctional microbe is required to have two or more functions. Before a multifunctional test is performed, the microbes must be tested and confirmed, they are not pathogenic. The purpose of this research was to study phytopathogenicity, hemolysis and microbial ability in solubilizing phosphate and phosphate. The research procedure consisted of phytopathogenicity test, hemolysis test, the test of phosphate solubilizing ability on Pikovskaya solid medium and potassium solubilizing ability on Alexandrov solid medium. Based on the results of phytopatgonecity tests on bacteria and fungi, all isolates are non-phytopathogenic. From the hemolysis test of bacterial isolate BPK 2, BPK 6 and BPK 7 caused total hemolysis. Based on the hemolysis test of fungi isolate SSIO 6 caused total hemolysis, FPF E1 and JK 6 caused partial hemolysis. Isolate BPK 5 has the highest index in solubilizing potassium (1.375), while isolate BPF 9 has the highest index in solubilizing phosphate (1.533). Keywords: Microbe, multifunctional, pathogenicity, phosphate solubilizing, potassium solubilizing